Keynes Betrayed? Review of Geoff Tily's 'Keynes's General Theory, the Rate of Interest, and Keynesian Economics: Keynes Betrayed' - Jan Toporowski (Intervention. European Journal of Economics and Economic Policies, 2008)
First paragraph: In these dissembling, Harry Potterish, times it is rare to find an ambitious book that reads up to its declared ambition. Geoff Tily's book is just such a work, and its aim is nothing less than to change our view of Keynes. This endeavour, much like unravelling the meaning of Marx's Capital, has become one of the great intellectual swamps of economics in which too many able and intelligent academics have lost their way and perished (intellectually, if not physically) in pursuit of phantom solutions to imagined puzzles. Keynes defies summary interpretation because of the range of his interests. He toyed wantonly with the presuppositions of his readers, deliberately used ambiguity as a rhetorical device and infused his concepts with special meanings (see below). Any new interpretation therefore requires a huge amount of research and above all the integration of a mass of seemingly contradictory analysis and opinion.
Keywords: 330